2011
DOI: 10.1590/s1808-86942011000500007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of symptom improvement following nasal septoplasty with or without turbinectomy

Abstract: Most studies show that objective measures to quantify and determine surgical success in the treatment of nasal obstruction do not correlate with subjective improvement as reported by patients. Aim To evaluate the subjective improvement of nasal symptoms in patients undergoing septoplasty with or without turbinectomy. Materials and methods A prospective study. We evaluated 72 septoplasty patients with or without partial inferior turbinectomy; the patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Patients of severe septal deviation report signifi cantly higher rates of snoring (24% in our study) and PND (60% in our study) when compared with mild/moderate cases which is around 3% for snoring 8,9 and 8% for PND 8,9 (this data was generated on comparing our results with the data available in current literature). In this study, most common region involving DNS was area 1 + 2 + 3 (48%) followed by area 2 + 4 + 5 (28%) and 1 + 2 + 3 + 4 (18%).…”
Section: Exclusion Criteriasupporting
confidence: 64%
See 1 more Smart Citation
“…Patients of severe septal deviation report signifi cantly higher rates of snoring (24% in our study) and PND (60% in our study) when compared with mild/moderate cases which is around 3% for snoring 8,9 and 8% for PND 8,9 (this data was generated on comparing our results with the data available in current literature). In this study, most common region involving DNS was area 1 + 2 + 3 (48%) followed by area 2 + 4 + 5 (28%) and 1 + 2 + 3 + 4 (18%).…”
Section: Exclusion Criteriasupporting
confidence: 64%
“…Most prevalent complaint in the patients of deviated nasal septum among study subjects was nasal obstruction (74%) followed by anterior nasal discharge (41%), headache (20%), sneezing (15%), postnasal drip (8%), epiphora (7%), hyposma (3%), bleeding (3%) and snoring (3%). 9 Again, there is a remarkable absence of any similar study on severe septal deviations.…”
Section: Resultsmentioning
confidence: 99%
“…Velasco et al, in their study on post-operative evaluation of nasal obstruction found that septoplasty with or without turbinoplasty had same improvement of all symptoms. 6 Study by Lee et al, found an overall improvement in nasal obstruction by 91% and also stated that powered endoscopic turbinoplasty is an ideal procedure to manage chronic hypertrophic rhinitis in adjunct to endoscopic septoplasty. 7 Study by Bandos et al, stated that improvement in relief of nasal obstruction was seen in 90% cases undergone by septoplasty with partial inferior turbinectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Leandro Castro Velasco et al [6] have shown that a prospective study which focused on evaluation of the main nasal symptoms, including nasal obstruction. It is found that septoplasty, with or without turbinectomy, resulted in improvement of all symptoms.…”
Section: Discussionmentioning
confidence: 99%